STUDI PENAMBAHAN TEPUNG RUMPUT LAUT (Eucheuma cotonii ) PADA MIE SAGU TERHADAP PENERIMAAN KONSUMEN - Pendi Parsiholan Gultom; Desmelati '; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractThis study was aimed to determine the effect of seaweed (Eucheuma cottonii) in flournoodles to consumer acceptance. The each concentration of seaweed (Eucheuma cottonii)flour was 0%, 10%, 20%, and 30%. Parameters was measured for organoleptic (taste, texture,color, and odor), and chemical analysis (moisture content, ash content, protein content, crudefiber, and water absorption). The research was conducted in the Fisheries ProcessingTechnology and Processing Chemical Laboratory, Faculty of Fisheries and Marine Sciences,University of Riau on June 2014. The results showed that 20% concentration of seaweedflour was the best treatment and most favorable by consumer acceptance with moisturecontent, ash content, protein content, crude fiber and water absorption was 10,34%, 9,34%,27,9%, 6,04% and 10,34% respectively.Keywords: Sago noodles, seaweed (Eucheuma cottonii) flour,